"Many old people taking care of old people": Experiences of older adults after Hurricane María in Puerto Rico. - Adrián J Santiago-Santiago; Jeffrey Ramos-Santiago; Eliut Rivera-Segarra (PLoS ONE)
The Puerto Rican population has presented demographic changes resulting in a greater proportion of older adults than almost any other country in the world, with an estimated 28% of the total population being over 60 years of age. A key public health issue in Puerto Rico (PR) is older adults' mental health and wellbeing. Located in the Caribbean, PR is prone to natural hazards such as hurricanes, which are a known threat to older adults' overall health and wellbeing. However, the needs of older adults in PR and their mental health have been largely neglected, especially in less visible and marginalized rural areas. Therefore, the main objective of this study is to examine the challenges and needs of older adults following Hurricane María in the rural towns of Adjuntas and Castañer, PR. We implemented an exploratory qualitative research design informed by the principles of Liming methodology. We used semi-structured interviews to gather data and analyzed it using thematic analysis. A total of 25 participants engaged in our interview process including older adults (n = 15) and community caregivers and leaders that provide services to older adults (n = 10). We present three main themes regarding older adults' experiences after Hurricane María: 1) Challenges to wellbeing (i.e, loneliness, lack of resources), 2) Relational solidarity (i.e., communal support, equitable resource sharing) and 3) La brega (i.e., adaption and autogestión). Older adults in Adjuntas and Castañer addressed the emergent challenges after Hurricane María such as loneliness and lack of resources by relying on their communities. These findings highlight the role of community support as a key component to understand and foster older adults' wellbeing following a natural hazard.